Tìm x, biết: 2x(x – 5) – x(3 + 2x) = 26.

Tìm x, biết:
2x(x – 5) – x(3 + 2x) = 26.

2 bình luận về “Tìm x, biết: 2x(x – 5) – x(3 + 2x) = 26.”

  1. 2x(x – 5) – x(3 + 2x) = 26
    2x. x + 2x. (– 5) – x. 3 – x. 2x = 26
    2x^2 – 10x – 3x – 2x^2 = 26
    (2x^2 – 2x^2) – (10x + 3x) = 26
    – 13x = 26
    x = 26 : (– 13)
    x = –2
    Vậy   x = -2.
     

    Trả lời
  2. Giải đápLời giải và giải thích chi tiết:
    2x(x-5) -x(3+2x) = 26
    ⇔ 2x^2 – 2x^2 – 10x – 3x = 26
    ⇔-13x = 26
    ⇔x = 26 : (-13)
    ⇔x=-2
    Vậy x=-2

    Trả lời

Viết một bình luận

Câu hỏi mới